Islamic Overview on Qabdh in Online Shopping at Shopee Marketplace - Hendra Karunia Agustine; Marhamatul Barokah (Program Studi Ekonomi Syariah (Muamalah), 2022)
Shopee apps is a marketplace-based mobile commerce application and it acts as an intermediary between the two. In the context of Islamic law, transaction process used in this application considered having severity issues, such as 1) how qabdh (transfer of ownership) in online shopping on the Shopee platform is implemented; and 2) how the implementation of the concept of qabdh online shopping on the Shopee platform is viewed from Islamic law perspective. The purpose of this study is to find out the concept of qabdh in online shopping on the Shopee platform and to review concept of qabdh from the Islamic law views. This research is a qualitative research which is descriptive in nature and tends to use qualitative data analysis. The results of this study show that the qabdh is cosnidered in accordance with sharia provisions. According to Islamic law view, the implementation of the concept of qabdh in online shopping on the Shopee platform has also been considered to fulfill the principles of agreement according to sharia.